1992
DOI: 10.1139/m92-219
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of selenate and selenite to elemental selenium by Wolinella succinogenes

Abstract: Cultures of Wolinella succinogenes were adapted to grow in the presence of 1 mM [Formula: see text] or 10 mM [Formula: see text]. Both selenium salts were reduced to red, amorphous, elemental selenium but only after the culture reached the stationary growth phase. Bacterial cells taken from a culture actively reducing selenium were examined by transmission electron microscopy and were found to have large, electron-dense granules in the cytoplasm. These granules were verified by energy-dispersive X-ray spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…Indeed, it is not just confined to the bacteria that are capable of dissimilatory reduction of Se oxyanions, as it has also been reported in Se-resistant bacteria. For example, electron micrographs of Wollinella succinogenes (43), Enterobacter cloacae (23), and Stenotrophomonas maltophilia (8) have all shown that spherical granules of Se(0) that were similar sizes were formed after cells were exposed to Se(IV) or Se(VI). Intracellular Se(0) granules have also been reported in cells of the photosynthetic bacterium Chromatium vinosum, although in this case the granules were generated by the lightinduced oxidation of H 2 Se rather than by the reduction of Se oxyanions (25).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is not just confined to the bacteria that are capable of dissimilatory reduction of Se oxyanions, as it has also been reported in Se-resistant bacteria. For example, electron micrographs of Wollinella succinogenes (43), Enterobacter cloacae (23), and Stenotrophomonas maltophilia (8) have all shown that spherical granules of Se(0) that were similar sizes were formed after cells were exposed to Se(IV) or Se(VI). Intracellular Se(0) granules have also been reported in cells of the photosynthetic bacterium Chromatium vinosum, although in this case the granules were generated by the lightinduced oxidation of H 2 Se rather than by the reduction of Se oxyanions (25).…”
Section: Discussionmentioning
confidence: 99%
“…Their presence in only the treatments containing living bacteria suggests that the occurrence of elemental selenium is directly related to bacterial metabolism [33,[41][42][43]. Previous investigations have observed both intracellular [42,44,45] and extracellular [46,47] Se particles of various sizes and the precipitation mechanisms vary with the bacterial species. A prior study attributed intracellular elemental Se precipitation to a detoxification mechanism as Se 0 particles were observed within discrete internal membranes in Bacillus selenitireducens [42].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…During microbial reduction, soluble oxidized selenium (SeO42-or SeO32-) is reduced to insoluble elemental selenium (Se"). Microorganisms that can mediate the selenium reduction reaction include Wolinella succinogenes, Desulfovibrio desulfuricans and Pseudonomas bacteria (Macy et al, 1989;Tomei et al, 1992;Tomei et al, 1995). The chemistry of selenium is closely related to sulfur because of the similarity of thQr electron structure which is demonstrated by the fact that they are in the same column in the periodic chart.…”
Section: Section 2 Chemical and Biological Processes For Contaminant mentioning
confidence: 99%
“…They found that efficiency of growth varied with electron donor-acceptor combinations and that differences in energy coupling occurred with the various bacterial strains. Tomei et al (1992) adapted cultures of WoZineZZu succinogenes to grow in the presence of 1 mM Se032-or 10 mM SeO42-which were reduced to red, amorphous, elemental selenium after the culture reached the stationary growth phase. Bacterial cells taken from an active, selenium-reducing culture were examined by transmission electron microscopy and found to have large, electron-dense granules in the cytoplasm which consisted of selenium.…”
Section: Section 3 Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation